2013
DOI: 10.1111/jpim.12067
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Brand Metaphors as Design Innovation: A Test of Congruency Hypotheses

Abstract: Metaphors are a common tool in brand design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Stories led to the identification of previously unknown customer problems, whereas metaphors helped spark ideas on the ways in which the customer problems could be solved. The current study extends previous NPD research (Noble et al, ) by showing how metaphors can complement stories in the generation of breakthrough ideas.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Stories led to the identification of previously unknown customer problems, whereas metaphors helped spark ideas on the ways in which the customer problems could be solved. The current study extends previous NPD research (Noble et al, ) by showing how metaphors can complement stories in the generation of breakthrough ideas.…”
Section: Discussionsupporting
confidence: 84%
“…From a marketing perspective, metaphors are known for their value in communicating new product benefits (Zaltman & Coulter, ). Experiments across product categories have shown the value of metaphors in conveying the brand positioning in marketing campaigns in the later stages of NPD (Noble et al, ). Although the knowledge management literature acknowledges the role of metaphors in juxtaposing concepts and creating new knowledge (Nonaka, ), empirical evidence is sparse.…”
Section: Literature Review and Theoretical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…At the syntactic level, recent research (Miller and Toman, 2015) has suggested that compared with syntactically simple slogans, moderately complex slogans stimulate deeper processing improving brand recall and interpretation. At the semantic level, quite a lot of research has been carried out into linguistic and visual metaphors in brand naming (Noble et al, 2013). However, as we have said, there is very little research on brand slogans.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Metaphors can also make brands appear more sophisticated, exciting (Ang & Lim, 2006), differentiated, and vivid (Noble et al, 2013). A reason these positive effects occur is that consumers often gain pleasure from processing and resolving arrangements of signs that are immediately difficult to understand, which semiotics theory refers to as "pleasure of the text" (Barthes, 1985).…”
Section: Effects Of Using Metaphorsmentioning
confidence: 99%